2017
DOI: 10.1371/journal.pone.0188179
|View full text |Cite
|
Sign up to set email alerts
|

Organization and characterization of genetic regions in Bacillus subtilis subsp. krictiensis ATCC55079 associated with the biosynthesis of iturin and surfactin compounds

Abstract: Bacillus subtilis subsp. krictiensis ATCC55079 produces the cyclic lipopeptide antibiotics iturin A–F as well as several surfactins. Here, we analyzed and characterized the biosynthetic genes associated with iturin and surfactin production in this strain. We aligned the sequences of each iturin and surfactin synthetase ORF obtained from a genomic library screen and next generation sequencing. The resulting 37,249-bp and 37,645-bp sequences associated with iturin and surfactin production, respectively, containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…shows structural similarities to surfactin [49]. The notable differences among these lipopeptides include the type of the amino acids, their peptide sequences, the branching of the fatty acid chain [63] and their biosynthetic genes present in different operons. The presence of fenA and other four polyketide genes have been detected in the bacterial genome, however, fengycin, bacillaene, difficidin, macrolactins and bacillomycin were not detected by LC-ESI-MS. Synthesis of these compounds may be condition specific and therefore were not synthesized during the antagonistic activity against the fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…shows structural similarities to surfactin [49]. The notable differences among these lipopeptides include the type of the amino acids, their peptide sequences, the branching of the fatty acid chain [63] and their biosynthetic genes present in different operons. The presence of fenA and other four polyketide genes have been detected in the bacterial genome, however, fengycin, bacillaene, difficidin, macrolactins and bacillomycin were not detected by LC-ESI-MS. Synthesis of these compounds may be condition specific and therefore were not synthesized during the antagonistic activity against the fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Most Bacillus sp. can produce one type of lipopeptide and a few can produce two or three types of lipopeptides [13,14,15]. The biological activities of lipopeptides are closely related to the sequence of amino-acid residues, the cyclization of the peptide, and the length and branching of the fatty acid chain [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a Bacillus subtilis subsp. krictiensis surfactin-less mutant showed significantly higher antifungal activity against Fusarium oxysporum than its wild-type strain (41). Thus, we speculate that by reducing or preventing the biosynthesis of surfactin, BsA01 could avoid some negative impact on fitness while making an effective use of other inhibitory compounds against S. terrestris .…”
Section: Discussionmentioning
confidence: 99%
“…One could think that the lack of surfactin is a mere consequence of the metabolic change that arise along with the phenotype variation experienced by BsA01 and that is not directly related to the antagonism per se . However, it has been suggested that surfactins could interfere with the activity of other lipopeptides with proven antifungal activity such as fengycins/plipastatins and iturins (38, 41). In a study, B. amyloliquefaciens FZB42 mutants selectively repressed in the synthesis of one or two types of lipopeptides revealed that the co-production of surfactin and fengycin lowered the global antifungal activity (38).…”
Section: Discussionmentioning
confidence: 99%